INTRAOPERATIVE MITOMYCIN-C, 5-FLUOROURACIL, RETROBULBAR TRIAMCINOLON ACETONIDE, IS IT EQUALLY EFFECTIVE TO DECREASE INTRAOCULAR PRESSURE AFTER TRABECULECTOMY? - Sari, Yessi Primanda; Ekantini, Retno; Gani, Tatang Talka; Jati, Krisna Dwi Purnomo (Majalah Oftalmologi Indonesia, 2023)
Objectives: To evaluate the effect of mitomycin-C (MMC), 5-fluorouracil (5-FU), and retrobulbar triamcinolone acetonide (TA) on the surgical result of trabeculectomy Materials and Methods: All consecutive trabeculectomies with releasable sutures performed in Sardjito General Hospital between January 2022 and December 2022 were retrospectively reviewed from medical records. Patients without any intraoperative metabolite (control group, n=5) were compared to those with retrobulbar TA (n=5), MMC group (n=19), and 5-FU group (n=11) in terms of surgical success. Successful surgery results were defined as IOP between 5 - 21 mm Hg without any further medications or surgical intervention and fewer complications. Results: 40 eyes of 35 patients (15 male, 25 female, mean age 52.4 years) were included in the study. The IOP pre operative in TCA group was 47.12 ±12.16 mmHg, in MMC group was 35.53 ± 17.05 mmHg, in 5-FU group was 34.54 ± 17.77 mmHg, and 43.80 ± 15.79 mmHg in group without any metabolite. The patient was observed until the post-operation day (POD) 90. There were no significant differences in intraocular pressure at POD 1, 7, 30, 60, and 90 between the control group compared to TCA, MMC, and 5-FU group. In TCA group, pre operative IOP was 47.12 ±12.16 mmHg then decreases to 15.60 ± 4.61 mmHg at POD 90. In MMC group, pre operative IOP was 35.53 ± 17.05 mmHg, 90 days later became 14.42 ± 5.71 mmHg. In 5-FU group, pre operative IOP was 34.54 ± 17.77 mmHg then decrease to 13.64 ± 4.08 mmHg. In group without metabolite, pre operative IOP was 43.80 ± 15.79 mmHg, then became 21.00 ± 6.81 mmHg at POD 90. The lowest mean intraocular pressure of POD 90 was in the 5-FU group (13.64 ± 4.08 mmHg). Complication after trabeculectomy in the TCA group was 21%, the MMC group was 27%, the 5-FU group was 10%, and the control group was 42%. Conclusion: MMC, 5-FU, and TCA in this study are equally effective to decrease IOP after trabeculectomy.